Analysis of Mother's Day Celebration via circular statistics. - Abuzaid, Ali H. (Philippine Statistician, 2012)
This paper, handles with much emphasis, Mother's Day celebration around the world - a day that is celebrated on various days in different countries. These days are marked in relation to certain historical, religious or mythical events for every nation.